(untitled) (Historia, 2021)
English The delicate distinction between Voortrekkers and Trekboers On 5 December 1834 white Afrikaner farmers on the northern boundary of the Cape Colony, which roughly corresponds to the present day Colesberg district and environment, addressed a letter to the Cape Governor, Sir Benjamin D’Urban. They pointed out that they did not own any land and maintained that if the government were not prepared to allow their occupation of land north of the Orange River, they would be forced to sever ties with the Government and the Colony and take up residence to the north of the river where they, inevitably, would be independent from the British government. In search of pasturage, these farmers, who admitted to regular migrations, moved for longer periods of time to the north of the Orange River where some of them settled semi-permanently. This article demonstrates that, despite the well-known differences in motives and loyalty between the "Voortrekkers" and the "trekboers", the distinction between the two groups was in fact subject to change and difficult to maintain; that a substantial number of the "trekboers" were sympathetic to "Voortrekker" ideals and eventually associated themselves with the latter. Also included are a verbatim transcription of the letter to the Governor and an alphabetical list of signatories. Afrikaans Blanke Afrikanerboere op die noordgrens van die Kaapkolonie, teenswoordig ongeveer die distrik Colesberg en omgewing, het goewerneur sir Benjarnin D’ Urban in Desember 1834 daarop gewys dat hulle nie grond besit nie en indien die regering hulle nie sou toelaat om noord van die Oranje grond in besit te neem nie, hulle hul van die regering en Kolonie sou losmaak en dan verplig sou wees om ’n outhanklike bestaan in die Transoranje te voer. Hierdie manne was almal self-erkende "trekboere" wat ter wille van weiveld vir hulle vee lang rukke oorkant die grens vertoef het. Sommige van hulle het al bykans permanent in die Transoranje gewoon. Dié artikel toon aan dat, ondanks die bekende verskille in motiewe en lojaliteite tussen die "trekboere" en "Voortrekkers", hierdie onderskeid veranderlik en moeilik waarneembaar was; dat ’n stewige persentasie van die "trekboere" eintlik Voortrekkergesind was en hulself uiteindelik by laasgenoemde geskaar het. Verder word die versoekskrif tesame met die name van ondertekenaars hier verbatim weergegee.